Virtual HRD's Role in Crisis and the Post Covid-19 Professional Lifeworld: Accelerating Skills for Digital Transformation. Issue 1 (February 2021) - Bennett, Elisabeth E.; McWhorter, Rochell R.
The Problem: The Covid-19 pandemic brought unprecedented crisis to a world already undergoing digital transformation. Millions of people began working virtually to prevent the spread of disease and to maintain business continuity, suddenly participating in virtual human resource development (VHRD) and alternative work strategies that helped organizations adapt to current challenges and prepare for future disruption. The purpose of this article is to analyze VHRD's role in the crisis and the transition to a new era marked by further disruption and change. The Recommendation: This article provides a primer for understanding the environmental perspective of VHRD, analyzes reskilling and upskilling trends during the pandemic and for early stages of the fourth industrial revolution, and addresses learning, adaptation, cultural, workplace, and economic implications. We argue that many of the changes to the workplace were already underway, but the pandemic has accelerated transformation. For this reason, organizations must anticipate more digital transformation, strategize VHRD, and leverage learning assets to prepare for the future. The Stakeholders: This article is of interest to those helping their organizations to not only recover from crisis, but to thrive in a new era of work that is being fundamentally transformed by technology. The audience includes organizational leaders, HRD professionals, workers, scholars, as well as school personnel seeking to prepare learners for future career conditions.